2022
DOI: 10.4271/2022-01-1178
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corrosion on Particle Emissions from a Grey Cast Iron Brake Disc

Abstract: Reducing exhaust emissions has been a major focus of research for a number of years since internal combustion engines (ICE) contribute to a large number of harmful particles entering the environment. As a way of reducing emissions and helping to tackle climate change, many countries are announcing that they will ban the sale of new ICE vehicles soon. Electrical vehicles (EVs) represent a popular alternative vehicle propulsion system. However, although they produce zero exhaust emissions, there is still concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…As a result, the components of the braking systems might undergo corrosion during service. In particular, the brake discs are particularly exposed to corrosion due to the intrinsic low corrosion resistance of the gray cast iron in aggressive environments [ 50 , 51 ]. As discussed above, corrosion affecting the braking system of BEV, HEV, and PHEV vehicles is a critical aspect not only regarding the braking performance but also the emission of particulate matter.…”
Section: Corrosion-related Phenomena In Braking Systemsmentioning
confidence: 99%
“…As a result, the components of the braking systems might undergo corrosion during service. In particular, the brake discs are particularly exposed to corrosion due to the intrinsic low corrosion resistance of the gray cast iron in aggressive environments [ 50 , 51 ]. As discussed above, corrosion affecting the braking system of BEV, HEV, and PHEV vehicles is a critical aspect not only regarding the braking performance but also the emission of particulate matter.…”
Section: Corrosion-related Phenomena In Braking Systemsmentioning
confidence: 99%
“…But the reduced usage of brake pads can cause moisture to build-up on surface of brake pads instigating corrosion. Ghouri 82 carried out corroded and uncorroded test to see the effects of corrosion on particle emissions from GCI brake rotor. It was observed that the braking performance is affected by corrosion as it reduced the contact area between friction couple.…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…However, poor corrosion resistance and excessive wear result in high brake particle emissions. For example, a study found that the effect of corrosion inhibited braking performance by reducing the coefficient of friction and significantly increased both the number and mass of particle emissions by at least a factor of 2 and up to 30 times compared with the uncorroded disc under the same test conditions [13]. Various treatments (e.g., cryogenic, heat) can improve the tribological properties and reduce the wear [14].…”
Section: Introductionmentioning
confidence: 99%